Collecting Data in Forbidden Places: Reflections on Gaining Access, Mitigating Risks, and Managing Fieldworkers in Geopolitically Sensitive and Precarious Situations - Hamid Azizi; R. V. Gundur (International Journal of Qualitative Methods)
Undertaking research with hard-to-reach, criminogenic populations in unstable and violent political environments presents significant challenges and risks to researchers, fieldworkers, and participants. Key issues to consider in such undertakings include obtaining approval from university ethics committees, gaining access to hard-to-reach participants, and devising strategies to mitigate risks. Additionally, understanding the costs of such research is critical, especially for self-funded researchers planning to conduct fieldwork in geopolitically sensitive and precarious situations. This article, drawing upon a study that engaged with active drug traffickers and opium poppy farmers in Afghanistan after the country was taken over by the Taliban in August 2021, documents a novel approach to navigate these challenges. The article outlines how researchers gained access to active drug traffickers and opium poppy farmers in Afghanistan. It details the concerns raised by a university ethics committee about the project and discusses the strategies employed to mitigate risks to researchers, fieldworkers, and participants. Furthermore, the article provides a breakdown of the costs associated with conducting such fieldwork. It concludes by offering practical guidelines for researchers planning to collect data from hard-to-reach populations, whether in Afghanistan or similarly complex field locations.